Tantangan Duta GenRe sebagai Agen Advokasi Isu Kesehatan Reproduksi Remaja di Sleman, DIY - Ferdeo, Ferdeo (Umbara, 2026)
As agents of KEMENDUKBANGGA/BKKBN in the mission of population regulation, Duta GenRe (Youth Generation Planning Ambassadors) occupy a strategic position in shaping youth awareness of reproductive health and bodily autonomy. While undergoing their own psychosocial development and identity formation, these adolescents are expected to become active agents in the biopolitical effort to prevent the Triad KRR. Their role is vital to achieving national goals of Indonesia Emas 2045 and aligning with global commitments under the Sustainable Development Goals (SDGs), particularly in good health and well-being. This study, employing a qualitative ethnographic approach in Sleman, identifies the multidimensional challenges faced by Duta GenRe, including societal taboos surrounding sexual and reproductive health, and internalized norms of masculinity that hinder open discourse. The prevalence of risky sexual behavior in Sleman—the so-called “Student City”—adds another layer of complexity. Notably, contradictions arise when some ambassadors themselves engage in behaviors they are meant to prevent, revealing tensions between personal identity, institutional expectations, and public representation. To move forward, synergy across societal sectors must be strengthened, with support systems that go beyond symbolic recognition. Meaningful change requires empowering young people with accurate knowledge, safe spaces, and a critical, inclusive approach to reproductive rights. Only then can we ensure a generation that contributes responsibly to a healthier and more equitable Indonesia.